Peningkatan Produksi Beras terhadap perbaikan ekonomi masyarakat melalui Kerjasama Industri di kabupaten Pinrang - Beddu, Megawati; Modding, Basri; B, Herman (Amsir Community Service Journal, 2025)
Pinrang Regency is one of the main rice-producing areas in Indonesia with great agricultural potential. The management of rice production by local farmers still faces various challenges, such as lack of knowledge and skills in production management and limited use of modern technology. This problem has an impact on low productivity and quality of crops as well as difficulties in accessing a wider market, which ultimately affects the economic welfare of farmers. This research aims to increase the capacity of farmers through strengthening partnerships with rice industry mills and developing effective marketing strategies. The implementation of this research is divided into three stages: preparation, implementation, and monitoring and evaluation. Through coordination meetings, factory visits, and discussions, it is hoped that stronger cooperation and wider market access will be established. The success of this program indicates the importance of collaboration between farmers, industry, and the government in improving rice production management and the economic welfare of the community. This program is expected to be a successful model that can be replicated in other rice-producing regions